Accuracy of F-18 FDG PET/CT with optimal cut-offs of maximum standardized uptake value according to size for diagnosis of regional lymph node metastasis in patients with rectal cancer - Bae, Sung Uk (Cancer Imaging, 2018)
BACKGROUND: The low sensitivity of F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for the evaluation of metastatic lymph nodes (LNs) is mainly due to the partial volume effect in patients with rectal cancer. This retrospective study evaluated the diagnostic accuracy of F-18 FDG PET/CT with optimal cut-off values of the maximum standardized uptake value (SUV(max)), according to LN size, for the evaluation of regional LN in rectal cancer patients. METHODS: This study included 176 patients with rectal cancer who underwent F-18 FDG PET/CT for initial staging. Patients were classified based on the long-axis diameter of the regional LN on CT images as small (≤ 7 mm; n = 118) and large (> 7 mm; n = 58) LN groups. The optimal cut-off value of SUV(max) was determined for each group, using receiver operating characteristic curve analysis. Areas under the curve (AUC) were compared by C-statistics using two methods: the cut-off value of SUV(max) optimized according to LN size, and a fixed SUV(max) cut-off value of 2.5. RESULTS: The optimal cut-off values of SUV(max) for the small and large LN groups were 1.1, and 2.1, respectively. The sensitivity, specificity, and accuracy of F-18 FDG PET/CT using the optimal cut-off values were 90.6, 70.9, and 76.3% in the small LN group, and 68.6, 78.3, and 72.4% in the large LN group. The sensitivity, specificity, and accuracy of F-18 FDG PET/CT using the fixed cut-off value were 18.8, 100, and 78.0% in the small LN group, and 51.4, 87.0, and 65.5% in the large LN group. The AUC was significantly higher using the optimal cut-off values than the fixed cut-off value (0.808 vs. 0.594, p = 0.005) in the small LN group, but not in the large LN group (0.734 vs. 0.692, p = 0.429). CONCLUSIONS: Application of the lower cut-off value of SUV(max) improves the diagnostic performance of F-18 FDG PET/CT for the evaluation of small regional LNs in patients with rectal cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40644-018-0165-5) contains supplementary material, which is available to authorized users.